Biological activity of egg-yolk protein by-product hydrolysates obtained with the use of non-commercial plant protease - A. Zambrowicz; E. Eckert; M. Pokora; A. Dąbrowska; M. Szołtysik; Ł. Bobak; T. Trziszka; J. Chrzanowska (Chiriotti Editori, 2015)
Enzymatic hydrolysis leads to improved functional and biological properties of protein by-products, which can be further used as nutraceuticals and protein ingredients for food applications. The present study evaluated ACE-inhibitory, antioxidant and immunostimulating activities in hydrolysates of egg-yolk protein by-product (YP), generated during industrial process of delipidation of yolk. The protein substrate was hydrolyzed using non-commercial protease from Asian pumpkin (Cucurbita ficifolia). The reaction was conducted in 0.1 M Tris-HCl buffer (pH 8.0) at temperature of 37°C for 4 hours using different enzyme doses (100-1000 U/mg of substrate). The protein degradation was monitored by the determination of the degree of hydrolysis (DH), release of free amino groups (FAG) and by RP-HPLC. In the obtained hydrolysates we also evaluated biological activities. It was shown that the highest DH of substrate (46.6%) was obtained after 4h of reaction at the highest amount of enzyme. This hydrolysate exhibited antioxidant activity, including ferricion reducing (FRAP) (56.41 μg Fe2+/mg), ferric ion chelating (695.76 μg Fe2+/mg) and DPPH free radical scavenging (0.89 μmol troloxeq/mg) as well as ACE-inhibitory (IC50=837.75 μg/mL) activities. The research showed improved biological properties of enzymatically modified YP by-product.